2021
DOI: 10.1007/s00394-021-02539-7
|View full text |Cite
|
Sign up to set email alerts
|

Diet affects glycosylation of serum proteins in women at risk for cardiometabolic disease

Abstract: Background Glycoproteomics deals with glycoproteins that are formed by post-translational modification when sugars (like fucose and sialic acid) are attached to protein. Glycosylation of proteins influences function, but whether glycosylation is altered by diet is unknown. Objective To evaluate the effect of consuming a diet based on the Dietary Guidelines for Americans on circulating glycoproteins that have previously been associated with cardiometabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…One study found dietary habits influencing interesting changes in plasma N-glycosylation. 36 Increased sialylation was positively associated with a healthier diet, which is opposite to the commonly observed higher abundance of highly sialylated (trisialylated and tetrasialylated) glycans in individuals with various diseases. Since IR is a known driving factor for T2DM development and its key feature, in addition to previous findings, this study investigated whether plasma N-glycome is predictive of first clinical diagnosis of impaired glucose metabolism, incident IR or T2DM in 534 individuals (89 incident IR/T2DM cases, 445 controls) from the TwinsUK cohort with independent replication.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…One study found dietary habits influencing interesting changes in plasma N-glycosylation. 36 Increased sialylation was positively associated with a healthier diet, which is opposite to the commonly observed higher abundance of highly sialylated (trisialylated and tetrasialylated) glycans in individuals with various diseases. Since IR is a known driving factor for T2DM development and its key feature, in addition to previous findings, this study investigated whether plasma N-glycome is predictive of first clinical diagnosis of impaired glucose metabolism, incident IR or T2DM in 534 individuals (89 incident IR/T2DM cases, 445 controls) from the TwinsUK cohort with independent replication.…”
mentioning
confidence: 75%
“…Apart from being associated with various diseases and disorders, plasma N-glycosylation has been thoroughly examined in association with lifestyle factors, such as smoking, 33 exercise, 34 sleep 35 and dietary habits. 36 While smoking influenced increase in complexity of glycans, 33 which is associated with a proinflammatory-like glycosylation profile, moderate to vigorous exercise positively affected the plasma glycosylation profile of older female individuals despite them being diagnosed with metabolic syndrome by decreasing levels of triantennary and tetra-antennary glycans, 34 both hallmarks of complex plasma glycoprofile. Interestingly, higher abundance of biantennary glycan structures with core fucose and one or two sialic acid residues was observed in patients with rapid eye movement sleep behavior disorder when compared with healthy controls.…”
mentioning
confidence: 99%
“…A better understanding of the interaction between nutrition and ageing is essential to unravel the mechanisms responsible for these positive/negative effects, to identify diet components promoting the quality of life in old age and to contribute to the prevention of late-life disabilities [ 14 ]. Few studies have shown how the dietary patterns in humans affect glycosylation, however there is evidence that diet may influence disease state by altering glycosylation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in glycosylation have been reported in metabolic diseases like fatty liver disease, diabetes, and NASH ( 6 , 20 , 47 , 48 , 49 ). The use of serum glycan markers is the most common method to identify specific N-linked glycan alterations that can be utilized for biomarkers strategies in fatty liver disease and NASH ( 7 , 19 ).…”
Section: Discussionmentioning
confidence: 99%